(untitled) (LIS TODAY, 2025)
This study explores the integration of Information and Communication Technology (ICT) in school libraries and its impact on digital literacy and the evolving roles of school librarians within the context of India’s National Education Policy (NEP) 2020. A structured survey was conducted with 300 school librarians, teachers, and administrators from various educational institutions, including public and private, urban and rural schools. The survey aimed to evaluate the extent of ICT integration, the digital literacy levels of librarians, and how these factors influence their professional roles. The study also identifies key challenges to effective ICT integration, including infrastructural limitations and the need for enhanced professional development. These findings offer valuable insights and practical recommendations to align with NEP 2020’s goals of leveraging technology to improve educational outcomes and support the evolving roles of school librarians in promoting digital literacy and managing information effectively.